The Survival of the Royals - Alberto Batinti; Joan Costa-Font; Vasuprada Shandar (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We study the effect of royalty status - historically rooted legal privilege enjoyed by hereditary monarchs - on human longevity, a proxy of individuals' health capital. We disentangle royalty status that encompassed serving as heads of state, and hence subject to status-related stress, from other family members alongside their contemporary countrymen. We exploit a dataset containing relevant demographic data and specifically the lifespan (age at death) of European Royals and their families spanning the past three centuries (1669 to 2022) from the sixteen European countries, including information for 845 high-status nobility and relative monarchs which is compared to otherwise similar countrymen by adjusting for relevant confounders. We document robust evidence of a statistically significant gap in life expectancy between monarchs and other members of the royal family, as well as between monarchs and the general population of an average of 5.2 to 7.1 years longer than their contemporaneous countrymen.
Keywords: I18; N13; P00; 330; royal family; monarchy; life expectancy; health inequality; social determinants of health; healthy lifestyles; universal health insurance; age at death